Evidence for a role of ACTN3 R577X polymorphism in football player`s career progression - Barbosa Coelho, D.; Mendonça Pimenta, E.; Cruz Rosse, I.; Magalhães de Castro, B.; Kappes Becker, L.; Cruz de Oliveira, E.; Santos Carvalho, M. R.; Silami Garcia, E. (International Journal of Sports Medicine, 2018)
The aim was to investigate a possible role of the ACTN3 R577X polymorphism in a Brazilian football player`s career progression. 2 questions were formulated: 1. Does ACTN3 polymorphism affect the probability of an individual being a professional football player? 2. Does this polymorphism affect the progression of the athlete throughout his career? The study included 353 players from first division Brazilian football clubs in the following categories: under-14 (U-14), U-15, U-17, U-20, and professional (PRO). The control group (CON) was composed of 100 healthy non-athletes. The chi-squared test was used to assess differences between the allele and genotype frequencies. Comparing football categories, the XX genotype was less frequent among professional players than in the U-20 (p<0.05) or the U-15 category (p<0.05). The RX genotype also presented more frequently in the PRO category than the U-14 category (p<0.05). Moreover, a trend towards a higher frequency of the RX genotype and a lower frequency of the XX genotype was observed in the professional category compared to U-20. These results suggest that the genotype in the ACTN3 polymorphism affects the probability of a football player progressing throughout his career and becoming professional, meaning that playing football selects against the ACTN3 XX genotype.